Starstrike - Lee, Yoon Ha (Lee, Yoon Ha. Moonstorm trilogy, 2025)
"Teen mecha pilot Hwa Young returns to her rebel roots to fight against the Imperial force, but as she grapples with her warring allegiances, who can she really trust?"--